118 High-resolution cardiac magnetic resonance perfusion imaging vs positron emission tomography for the detection and localisation of coronary artery disease. (9th June 2011) - Morton, G D J; Ishida, M; Chiribiri, A; Schuster, A; Baker, S; Hussain, S; Perera, D; O'Doherty, M; Barrington, S; Nagel, E
Abstract : Background: Non-invasive imaging has a key role in the detection of coronary artery disease (CAD). Its importance has been affirmed by recent National Institute of Clinical Excellence (NICE) guidelines. Localisation of ischaemia to a coronary territory is also important in patient management. Cardiac Magnetic Resonance (CMR) perfusion imaging is a well-established and radiation-free test for these purposes. However, there are few data comparing perfusion CMR with Positron Emission Tomography (PET), which is widely regarded as the non-invasive gold standard. Furthermore novel CMR methods, including those based on k-t acceleration techniques, allow myocardial perfusion imaging with unprecedented spatial resolution. Methods: 31 patients with known or suspected CAD referred for diagnostic x-ray coronary angiography (XCA) underwent both CMR and PET examinations. Both PET and CMR protocols included adenosine stress and rest perfusion imaging. CMR perfusion imaging was performed at 1.5T with a k-t -accelerated steady-state free-precession sequence. PET imaging was performed with 13 N-Ammonia. The Abstract 118 figure 1 shows an example. Experts blinded to the clinical data analysed the imaging data and experts blinded to the imaging results visually analysed the XCA data. A significant coronary artery stenosis was defined as ≥70% reduction in diameter or a fractional flow reserve <0.8 where available. Sensitivity and specificity for PET and CMR vs invasive angiography were calculated. Localisation of ischaemia was assessed in patients with CAD by classifying myocardial territories as either supplied by, or remote from, a stenotic artery. Results: Patient characteristics are shown in the Abstract 118 table 1 . Mean age ± SD was 64±9 years. One CMR examination was non-diagnostic. The interval between PET and CMR was 2±6 days (77% same day), between PET and XCA 22±28 days and between CMR and XCA 22±29 days. The prevalence of CAD was 81%. For the detection of CAD PET sensitivity was 80% (95% CI 59% to 92%) and specificity was 67% (24% to 94%). CMR sensitivity was 83% (95% CI 62 to 95%) and specificity was also 83% (36% to 99%). In patients with CAD ischaemia was localised to 63% of the territories supplied by stenotic arteries by PET and 76% by CMR. Remote ischaemia was detected in 24% of territories by PET and 16% by CMR. Conclusions: CMR is at least as accurate as PET for the diagnosis of CAD and also for the localisation of ischaemia to coronary territories. Relatively low numbers mean that CIs are wide and further work is required. Using an anatomic test as the reference-standard for functional tests has well-described limitations. Remote ischaemia is likely to occur for several reasons including underestimation of disease severity at XCA, microvascular disease and also false positive results.